Primary and secondary school in Novokuznetsk - Валерий Цой; Дмитрий Тельгереков; Роман Собольников (Проект Байкал)
The article considers the space-planning solution for the school building designed by AB PRO and the existing constraints, which influenced the formation process. The article features the tasks, which were faced by the author, and their solutions.